AB0735 Diagnostic Delay Worsens Mobility and Work Disability in Ankylosing Spondylitis. (10th June 2014) - Gunasekera, W.; Shaddick, G.; Jobling, A.; Smith, A.; Sengupta, R.
Abstract : Background: Diagnostic delay (DD) in Ankylosing Spondylitis (AS) remains a challenge, averaging 8.6 years 1 . Chronic back pain comprises 2.6million GP consultations per year, of which 5% have AS 2 . Identifying this "needle in a haystack" is compounded by poor appreciation of inflammatory back pain and lack of appropriate use of MRI early in diagnosis. The advent of biologic therapy with potential to induce remission makes early diagnosis increasingly important. There is paucity of data on the impact of DD on disease burden in AS. Published data suggests DD correlates to high disease activity, functional impairment, poor metrology and work disability (WD) 3, 4 . DD and WD correlate to reduced survival in AS 5 . Objectives: Primarily to assess the impact of DD on Bath AS Metrology Index (BASMI) and current work status (cWS) Secondarily to assess the impact of DD on Bath AS disease activity Index (BASDAI), Bath AS Functional Index (BASFI) and current Tumour Necrosis Factor inhibitor use (cTNFU) Methods: This was a retrospective cohort study of AS patients meeting modified New York criteria. Time from symptom onset to diagnosis (DD) was correlated to BASMI, BASDAI and BASFI within a year of diagnosis, cWS in those under 60 years and cTNFU. The confounding effects of age, HLA B27 status, family history of AS and smoking were accounted for by statistical modelling Results: Data on 106 patients was analysed. 79% were male. Mean age at symptoms onset was 24.5years (±SD 9.8) and at diagnosis was 35.5 (±14.0). Mean DD was 10.5 (±11.9). Gender made no significant difference to DD (p=0.4) BASMI score increased by 0.06 for each year of DD (p=0.0002) and age at diagnosis (p=0.015) when measured independently. However when DD was corrected for age the BASMI rise was not significant, indicating that age remained a significant predictor (p=0.039) 33% of patients were Work disabled (WD). Gender had no significant impact on cWS (p=0.1). The Work enabled (WE) had significantly shorter DD than the WD (median 7.8 vs. 16.6 years, p=0.005). The risk of being WD increased by 6.6% for each year of DD (OR=1.067, CI=1.03–1.1; p=0.0009) Age at diagnosis was a significant predictor of cWS (p=0.008). The risk of being WD increased to peak at 38.5 years and declined thereafter. HLA B27 positive patients had 6 fold higher odds of being WE (OR=6.2, CI=1.6–24.8) DD did not have a significant effect on BASDAI (p=0.8), BASFI (p=0.6) or cTFNU (p=0.9) Conclusions: DD caused significantly worse mobility and WD. Both outcomes were highly dependent on age at diagnosis. The peak risk of WD was in the age group that contributes the most to family and national economy. Unlike the published data, we did not find a significant impact of DD on BASDAI, BASFI or cTNFU. Our findings underpin the importance of minimising DD in AS. References: Hamilton L et al. Services for people with Ankylosing Spondylitis in the UK-a survey of Rheumatologists and patients. Rheum 2011;50:1991-8 Underwood MR et al. Inflammatory Back pain in primary care. Br J Rheum 1995;34(11):1074-7 Aggarwal R et al. Diagnosis delay in patients with Ankylosing Spondylitis:Factors and outcomes–an Indian perspective. Clin Rheum 2009;28:327–31 Cakar E et al. Work disability in ankylosing spondylitis:difference among working and workdisabled patients. Clin Rheum 2009;28(11):1309-14 Backland G et al. Increased mortality in ankylosing spondylitis is related to disease activity. Ann Rheum Dis 2011;70(11):1921-5 Acknowledgements: Royal National Hospital For Rheumatic Disease Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4528